Hubungan self-efficacy dengan self-management behaviour pada pasien hipertensi di rumah sakit umum daerah Majene - Patma, Patmawati; Yunding, Junaedi; Harli, Kurnia; Amin R, Muhammad (Journal of Health Education and Literacy, 2021)
Hypertension is a chronic disease, which can be managed non-pharmacologically by modifying lifestyle and self-management such as self-integration, socializing, and monitoring blood pressure. Self-management behavior (SMB) is an effective way for patients to manage behavior, improve patient health status, and independency to prevent complications in hypertension. One of the factors that influence the application of SMB is self-efficacy. The purpose of this study was to determine the relationship between self-efficacy and self-management behavior in hypertensive patients. This study used an observational analytic design with a cross-sectional study method. There were 77 hypertensive patients as samples obtained by using a purposive sampling technique which was analyzed by using the chi-square test. The results showed that there was a significant relationship between self-efficacy and self-management behavior in hypertensive patients (p = 0,000).